Динамическая модель распределения сетевых ресурсов с поддержкой гарантированного качества обслуживания в территориально-распределенных ткс - Симоненко, Д. В. (УНДІЗ, 2008)
This article proposes the development of dynamic model of network resources allocation model by introducing additional conditions of guaranteed quality of service. Proposed conditions are presented as QoS constraints for optimization task. QoS constraints succeded to be formulated in analytical form owing to tensor interpretation of mathematical telecommunication network model.
Keywords: динамическая модель; распределение; сетевые ресурсы; QoS